PERAN WANITA KARIER DALAM MENCIPTAKAN KELUARGA SAKINAH - Mahmudah, Siti (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2008)
There`s no prohibition in Islam for a wife to become a career woman. On the contrary, Islam encourages all Muslims including women to work and to be career women as long as their works are in accordance with their natures. There are many ways that can be performed by a career woman to help creating a happy family. A career woman as a wife, she must always keep allegiance to her husband. She must be able to convince her husband that she is a good wife, her life and all what she does is only devoted to her family. As a mother, a career woman must consistently take care and educate her children. As a social member, she must actively participate in social activities. All her activities must be done in balance without neglecting the one for the others. Keywords: career woman, Islam, happy family